Protecting marginalized groups during economic downturns : lessons from the Asian experience - Economic and Social Commission for Asia and the Pacific, Development Research and Policy Analysis Division; Sarkar, Hiren; Kumar, Raj (New York : United Nations, 2002)
This publication is based on the findings of an ESCAP project established to evaluate the effectiveness of government programmes and policies designed to alleviate the socio-economic impact of rising unemployment levels and income loss caused by the Asian economic crisis. The surveys covered the three hardest hit countries: Indonesia, the Republic of Korea and Thailand.
Includes Annexes (p. 73-136).
Keywords: Economic crisis; Social services; Informal sector; Economic integration; Social impact of Asian economic crisis; Microcredit; Unemployment insurance; Social security; Financial crises--Social aspects; Asia and the Pacific; Republic of Korea; Indonesia; Thailand; ESCAP